Dynamics Verification Experiment of the Stewart Parallel Manipulator. (16th October 2015) - Shao, Zhu-Feng; Tang, Xiaoqiang; Wang, Liping
As the basis of dynamic analysis and driving force calculation, dynamic models and dynamic parameters are important issues in mechanical design and control. In this paper, a dynamics verification experiment, which covers both dynamic models and dynamic parameters as a whole, is carried out on the typical Stewart parallel manipulator. First, the complete dynamic model of the Stewart manipulator is derived, considering the force sensors. The Newton-Euler method with clear physical meaning is adopted to facilitate understanding and parameter definitions. The dynamic parameters are deduced based on the established three-dimensional virtual prototype and adjusted with actual measurements. The recorded trajectory, instead of the theory trajectory, is adopted to calculate the theoretical limb forces. The practical limb forces are measured using pull pressure sensors. Finally, the dynamic model and identified parameters are verified by comparing the limb forces obtained using the above two approaches. Experiment results show that theoretical and practical limb forces coincide well, with a small maximum RMS (root mean square) error of 1.516N and forces ranging from 10N to 40N. Additionally, the established dynamics verification algorithm, which involves dynamic modelling, a parameter identification approach and a data analysis method, are generic and practical, and can be flexibly applied to the dynamic analysis of other parallel manipulators.